Analysis of Education and Work Training to Prevent Prospective Sharia Insurance Agents Performing Fraud Criminal Acts in Marketing Products to Prospective Customers (Case Study at PT. Asuransi Prudential Syariah Binjai) - Prabowo, Bayu; Anggraini, Tuti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Good education and training not only make an employee in a company progress, but the company will also develop in a better direction, and of course be able to compete with bigger companies. The purpose of this research is to analyze the importance of education and job training to prevent prospective Sharia insurance agents from committing criminal acts of fraud in marketing products to prospective customers. This research was conducted using qualitative methods through case studies at PT. Asuransi Prudential Syariah Binjai. The results of this study indicate that good education and job training can make a professional agent and can prevent fraud against prospective customers. A good education can provide knowledge about products and applicable regulations, as well as make agents more skilled in providing correct information to prospective customers. Good job training can also make agents more responsible and disciplined in marketing their products and not carelessly using marketing techniques to get customers. The company’s concern for agent job education and training will have a significant influence on improving the quality of the company’s human resources.